Endovascular Embolization of the Uterine Arteries in Giant Uterine Fibroids - B. M. Sharafutdinov; E. Yu. Antropova; S. A. Ryzhkin; A. F. Khalirakhmanov; I. V. Klyucharov; I. R. Galimova; M. I. Mazitova; M. K. Mikhaylov (Вестник рентгенологии и радиологии)
Choosing a treatment option for uterine fibroids is today one of the most relevant problems in gynecological practice. Thanks to the success of modern medicine and the increased level of the population’s culture, female patients seek medical help without waiting for the tumor to acquire significant sizes. However, in practice, there are cases when fibroids reach gigantic sizes. Hysterectomy is a traditional approach to treating uterine fibroids of these sizes according to the current clinical guidelines. The introduction of new high-tech treatments, such as uterine artery embolization, has led to a revision of radical surgery, by giving preference to alternative approaches especially in cases where the patient desires to preserve the reproductive organ. The paper describes a clinical case that confirms an individual approach to choosing a treatment option towards organ-sparing surgery for giant uterine fibroids. The use of endovascular embolization of the uterine arteries as a treatment for giant uterine fibroids is shown to be justified as an organ-sparing surgery if the patient desires to preserve reproductive function.